Assessment of Knowledge, Attitudes, and Practices around Cervical Cancer Screening in the Gulu District of Northern Uganda: A cross-sectional study - Tana Chongsuwat; Andre Nana; Aaliyah O Ibrahim; Ann E Evensen; James H Conway; Sumba O Pius; Ibrahim Sseddangira; Usman Iqbal; William Oloya (International Journal for Quality in Health Care, 2026)
Abstract Background Cervical cancer is a global health issue, particularly Sub-Saharan Africa including Uganda, where it poses a severe burden. Despite the availability of screening methods, uptake remains low due to various barriers, such as limited resources and a lack of awareness. This study primarily aimed to assess the knowledge, attitudes, and practices related to cervical cancer screening among men and women in the Gulu District of Northern Uganda, with secondary objectives on understanding gender differences, the impact of HIV status, and identifying barriers to screening. Methods A cross-sectional study was conducted in December 2021 using a structured questionnaire administered in both English and Acholi to evaluate participants' knowledge of cervical cancer, attitudes towards the disease, and screening practices. We described knowledge, attitudes, and practices, and applied logistic regression to explore the associations between gender, HIV status, and correctness of responses. Results A total of 379 participants aged 18 years and above were included. Most respondents self-reported low overall knowledge of cervical cancer (n = 298 of 376 responses, 79.3%), which is reflected in the low percentage of correct responses to questions related to the recommended age for screening (1.9%) and the frequency of screening for HIV negative/unknown (4.5%), and HIV positive (9.8%) persons. Gender and HIV status among female respondents were not associated with knowledge levels. Stigma related to cervical cancer was reported among 40.8% of participants (n = 147 out of 360 responses. Most participants never had a pelvic exam for cervical cancer (n = 183 out of 258 responses, 70.9%) or testing for HPV (n = 198 out of 246 responses, 80.5%). Among women living with HIV- 41.7% (n = 20 of 48 respondents) reported having received a pelvic examination for cervical cancer screening, and 18.6% (n = 8 of 43 respondents) reported having been screened for HPV. The majority identified cost (n = 166 out of 273 responses, 60.8%) and access to healthcare facilities (n = 246 out of 373 responses, 66%) as barriers to screening. Conclusion The study highlights a low level of knowledge, understanding, and practice concerning cervical cancer screening, emphasizing the need for targeted interventions to reduce stigma and increase awareness of recommended screening intervals and risk reduction methods in Northern Uganda. Improving accessibility and affordability of screening services may also help reduce persistent structural barriers to screening.